The Efficiency of Happiness Training to Increase the Hope in Elderly People - Sara Firozeh Moghadam; Ahmad Borjali; Faramarz Sohrabi (University of Social Welfare & Rehabilitation Sciences, 2014)
Objectives: This research was performed with the purpose of determining the efficiency of happiness training to increase the hope in elderly people. Methods & Materials: The present research is of the applied, pre/post test semi-experimental research with unequal control group. In this research, 24 of the elderly people having the entering conditions were selected by using the available sampling method among the elderly people residing in Mashhad’s elderly person's house being put equally into two groups of experimental and control. Finally the results of 20 of them were studied due to drop out of subjects. Snyder hope questionnaire (1991) was used in order to gather the data. After performing the pre-test, the happiness training program was done in 10 group sessions for the experimental group. At the end of training, post test for two groups and in the follow- up stage the hope test was repeated for the experimental group. Covariance analysis and t paired were used in order to analyse the results. Results: The analysis of the result of the covariance indicated the meaningfulness of the relationship between the hope dependent variable and the independent variable on the level of P<0.05. The evaluation of the moderated averages of the hope variable in the control and experimental groups showed the orientation of the relationship. The comparison of the scores in the experimental group in the post-test stage with the follow-up stage via t paired test showed no difference in the variables of hope. Conclusion: Finding suggest that skills of happiness increase hope and the effect of happiness training on the hope was consistent in the follow-up stage.